Association between Oxidative Stress Biomarkers, Tumor Aggressiveness, and Hematological Abnormalities in Ovarian Cancer Patients: A Hospital-Based Study - Syeda Shaista Waheed, Hanana Hameed, Sajjad Ul Hasan, Muhammad Tariq Hamayun Khan, Sajida Imran, Faiza Nisar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ovarian cancer remains a leading cause of gynecologic cancer-related mortality, often diagnosed at advanced stages. Oxidative stress is increasingly recognized as a key contributor to tumor progression, while hematological abnormalities frequently reflect underlying tumor biology and systemic inflammation. Objective: To investigate the association between oxidative stress biomarkers, tumor aggressiveness, and hematological abnormalities in patients with epithelial ovarian carcinoma. Methods: This hospital-based cross-sectional study included 70 patients diagnosed with histologically confirmed epithelial ovarian cancer, recruited from the Departments of Obstetrics and Gynecology at Nawaz Sharif Medical College, Bolan Medical College Hospital, and Gulab Devi Teaching Hospital between January 2022 and April 2023. Serum levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were measured. Hematological parameters, including hemoglobin, white blood cell count, platelet count, red cell distribution width (RDW), and mean corpuscular volume (MCV), were analyzed. Tumor grade, FIGO stage, and Ki-67 index were used to assess tumor aggressiveness. Multivariate regression was used to identify independent predictors. Results: MDA levels were significantly elevated in high-grade and advanced-stage tumors (p < 0.001), while SOD and GPx levels were significantly reduced (p = 0.002 and 0.004, respectively). Anemia (74.2%), thrombocytosis (32.8%), and elevated RDW (64%) were commonly observed and strongly associated with oxidative imbalance and tumor severity. MDA and platelet count independently predicted tumor grade, whereas SOD and hemoglobin were independent predictors of FIGO stage (adjusted R² = 0.59, p < 0.001). Conclusion: Oxidative stress and hematological abnormalities are significantly associated with tumor aggressiveness in ovarian cancer. MDA, SOD, GPx, and routine hematologic indices may serve as accessible prognostic biomarkers, particularly in low-resource settings. Keywords: Ovarian cancer, oxidative stress, malondialdehyde, superoxide dismutase, glutathione peroxidase, tumor aggressiveness, hematological abnormalities.